KEPEMILIKAN MANAJERIAL DAN LEVERAGE SEBAGAI PREDIKTOR PROFITABILITAS DAN PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Agus Dwipayadnya, Putu; Wiagustini, Ni Luh Putu; Anom Purbawangsa, Ida Bgs. (Buletin Studi Ekonomi, 2016)
Managerial Ownership and Leverage as Profitability Predictor and Corporate Social Responsibility Disclosure. This study aimed to determine the effect of managerial ownership composition and leverage on profitability and disclosure of CSR. The population in this study are manufacturing companies listed in Indonesia Stock Exchange. Sampling was conducted research with purposive sampling method so that the sample of this study as many as 24 companies. The research data is secondary data obtained from the website of the Indonesia Stock Exchange and the Indonesian Capital Market Directory from 2009 until 2013. Testing research hypotheses using path analysis technique (path analysis). The results showed that: (1) managerial ownership and leverage impact positivelly on profitability. (2) managerial ownership effect negativelly on leverage. (3) managerial ownership and leverage do not affect the disclosure of CSR. (4) profitability impact positively on the disclosure of CSR. (5) profitability is able to mediate the relationship managerial ownership and leverage on CSR disclosure.   Keywords: Managerial Ownership, Leverage, Profitability and Corporate Social Responsibility Disclosure
Keywords: Managerial Ownership, Leverage, Profitability and Corporate Social Responsibility Disclosure